1990
DOI: 10.1111/j.1750-3639.1990.tb00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics and Molecular Genetics of Malignant Gliomas and Medulloblastoma

Abstract: Malignant gliomas and medulloblastomas which are the most common primary malignant brain tumours of adult and children, respectively, resemble other neurogenic tumours as they frequently contain gene amplification and show non-random loss of specific chromosomal regions. In gliomas the gene which is most often amplified, is the epidermal growth factor receptor gene. In many cases the gene is rearranged as well, producing abnormally small epidermal growth factor receptor proteins. More than 80% of tumours have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 41 publications
(34 reference statements)
6
52
0
1
Order By: Relevance
“…This is in keeping with the demonstration that loss of heterozygosity for loci on the short arm of chromosome 17 (17p) (where the p53 gene is located) is shared by cells in each malignancy stage (ElAzouzi et al, 1989;James et al, 1989James et al, , 1990Bigner & Vogelstein, 1990;Venter & Thomas, 1991;Cavenee, 1992;von Diemling et al, 1993). p53 gene and protein alterations could indeed be an early event in tumour progression, which may be associated with clinical aggressiveness.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This is in keeping with the demonstration that loss of heterozygosity for loci on the short arm of chromosome 17 (17p) (where the p53 gene is located) is shared by cells in each malignancy stage (ElAzouzi et al, 1989;James et al, 1989James et al, , 1990Bigner & Vogelstein, 1990;Venter & Thomas, 1991;Cavenee, 1992;von Diemling et al, 1993). p53 gene and protein alterations could indeed be an early event in tumour progression, which may be associated with clinical aggressiveness.…”
Section: Discussionsupporting
confidence: 50%
“…The fact that the recurrent tumours that we could analyse were histologically malignant (one grade III astrocytoma and four glioblastomas) could be related to the fact that, once a tumour is composed mainly of a p53-positive genetically unstable cell population (Lane, 1992), the likelihood of further genetic damage is greater and specific additional structural changes, for example on chromosome 10, could be more frequent, leading to the development of a highly aggressive tumour (Bigner & Vogelstein, 1990;von Diemling et al, 1993). In this view the four recurrences with histological features of glioblastomas could be interpreted as type 1 glioblastomas according to von Diemling et al (1993).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Molecular studies demonstrated the amplification of several genes in these tumors, especially of the EGFR gene; the amplified sequences were found located on dmin, analyzed in a small number of cases by in situ hybridization of tumor metaphases. 15,16 However, studies by FISH in interphase nuclei are more frequent, displaying a considerable heterogeneity of EGFR copy number.…”
Section: Discussionmentioning
confidence: 99%
“…8 The first evidence of gene amplification in glioblastoma was provided by cytogenetic analyses that exhibited the presence of dmin. 9,10 Molecular screening for gene amplification revealed frequent amplification of the EGFR, observed in about 35-70% of glioblastomas. 8,11,12 Differences in the frequency of EGFR amplification are most probably due to different methods used, such as Southern blot, polymerase chain reaction (PCR), and fluorescent in situ hybridization (FISH).…”
mentioning
confidence: 99%
“…Interestingly, although PTEN mutations are observed frequently in GBM, they are rare in lowergrade astrocytic tumors (Louis et al, 2007). Although the sequence of mutational events in primary GBM is unknown, in secondary GBM, TP53 mutation is usually an early event occurring frequently in lower-grade astrocytic tumors (Bigner and Vogelstein, 1990); however, PTEN inactivation is not detected frequently until the transition to GBM. This suggests that PTEN loss does not confer a selective growth advantage early in astrocytic tumor development (Figure 3).…”
Section: Somatic Mutation Of Pten In Brain Tumorsmentioning
confidence: 99%